2007
DOI: 10.1097/01.ccm.0000250357.35250.a2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anesthesia impairs the hemodynamic response to acute pulmonary hypertension by deteriorating right ventricular–pulmonary arterial coupling*

Abstract: Thoracic epidural anesthesia inhibits the native positive inotropic response of the right ventricle to increased afterload and deteriorates the hemodynamic effects of acute pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 48 publications
0
19
0
3
Order By: Relevance
“…Animal studies using invasive measurement techniques to measure contractile performance have found no significant effects of TEA on baseline right ventricular inotropic state. 25 As TAPSE is a loaddependent ejection index of right ventricular function, the observed increase could be due to either an increase in contractile performance and/or an increase in right ventricular preload as well as a reduction in right ventricular afterload. Estimated right ventricular systolic pressures, a surrogate for right ventricular afterload, slightly increased after TEA in our study, although Doppler indices of systolic function were inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…Animal studies using invasive measurement techniques to measure contractile performance have found no significant effects of TEA on baseline right ventricular inotropic state. 25 As TAPSE is a loaddependent ejection index of right ventricular function, the observed increase could be due to either an increase in contractile performance and/or an increase in right ventricular preload as well as a reduction in right ventricular afterload. Estimated right ventricular systolic pressures, a surrogate for right ventricular afterload, slightly increased after TEA in our study, although Doppler indices of systolic function were inconclusive.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, high thoracic epidural should not be used in patients with PH, because blockade of the sympathetic cardiac nerves at T1 and T4 has a negative inotropic and chronotropic effect. 242,243,279,292,293 General anaesthesia is unavoidable in many surgical interventions. In these patients, it gives good haemodynamic and respiratory control.…”
Section: Anaesthetic Techniques In Patients With Pulmonary Hypertensionmentioning
confidence: 99%
“…Die ESC/ERS-Richtlinien empfehlen die epidurale Anästhesie für geeignete elektive operative Eingriffe [5]. Tierexperimentelle Daten zeigen, dass bei gesunden Tieren eine epidurale Blockade die HPV durch Hemmung des sympathischen Nervensystems verstärkt [29] und unter Ruhebedingungen im Vergleich zur linksventrikulären Kontraktilität die Funktion des RV nicht durch eine thorakale Epiduralanästhesie eingeschränkt wird [30]. Unter physiologischen Bedingungen führt eine Erhöhung der RV-Nachlast (z.…”
Section: Regionale Anästhesieverfahrenunclassified
“…B. HPV) zu einer Steigerung der RV-Kontraktilität (ventrikulovaskuläres "coupling", [30]). Eine thorakale Epiduralanästhesie hemmt diese positiv-inotrope Antwort des RV auf eine akute Steigerung des PVR und führt zu einer Abnahme des HZV, ohne den systemischen Gefäßwiderstand, das Sauerstoffangebot und den Sauerstoffverbrauch oder den RV-Koronarfluss zu verändern [30,31]. Eine lumbale Epiduralanästhesie reduzierte hingegen den SVR, ohne die RV Kontraktilität zu beeinflussen [31].…”
Section: Regionale Anästhesieverfahrenunclassified